2022
DOI: 10.1021/acsomega.2c05468
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Dual-Fuel Diesel/Natural Gas High-Pressure Injection

Abstract: Dual-fuel diesel/natural gas direct-injection engine is promising and highly attractive due to its low-carbon emission and high thermal efficiency, and both high-pressure diesel and natural gas injections are critical for air−fuel mixing. This study presents an optical experimental investigation on the highpressure dual-fuel diesel/methane injection process based on a constant-volume vessel test rig. The results show that the diesel penetration process of the dualfuel injection experiences two stages: Stage I,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The results showed that the SPA increased with an increase in the CTL blending ratio, mainly because the viscosity of CTL fuel is lower than that of diesel fuel and plays a key role in fuel atomization. Simultaneously, the increase in IP enhanced the entrainment effect of the spray and promoted droplet fragmentation and atomization. , Overall, blending CTL fuel with diesel fuel improves the spray quality under non-evaporating conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the SPA increased with an increase in the CTL blending ratio, mainly because the viscosity of CTL fuel is lower than that of diesel fuel and plays a key role in fuel atomization. Simultaneously, the increase in IP enhanced the entrainment effect of the spray and promoted droplet fragmentation and atomization. , Overall, blending CTL fuel with diesel fuel improves the spray quality under non-evaporating conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, the increase in IP enhanced the entrainment effect of the spray and promoted droplet fragmentation and atomization. 31,32 Overall, blending CTL fuel with diesel fuel improves the spray quality under non-evaporating conditions.…”
Section: Non-evaporation Conditions (T = 300 K)mentioning
confidence: 99%